Point of retreat : a novel - Hoover, Colleen (New York : Atria Paperback, 2012)
Layken and Will's relationship has endured through hardships, heartache, and a cruel twist of fate, further solidifying the fact that they belong together. But the two lovers could not have expected that the things that brought them together may ultimately be the things that tear them apart. Their connection is on the brink of being destroyed forever and it will take an extraordinary amount of willpower to keep their love afloat
Keywords: Life change events -- Fiction